The Effect of Yoga on Substance Use Disorder: A Systematic Review - Putu Emy Suryanti; Ella Nurlaella Hadi (Media Publikasi Promosi Kesehatan Indonesia (MPPKI), 2025)
Introduction: Substance use disorder become pervasive global issue, and have the impacts on disability and mortality. Substance use disorder within the context of drug addiction is a multifaceted disorder characterized by recurrent psychological and physiological dysfunction resulting from the continued use of drugs. This systematic review aims to evaluate the impact of yoga as a complementary therapy for people with substance use disorder to promote yoga as complementary therapy in drug rehabilitation to prevent relapse. Methods: This systematic review utilised secondary data retrieved from four electronic databases: PubMed, SAGE, ScienceDirect, and SpringerLink. The keywords are: “yoga” and “substance use disorder”, used the Boolean Operator, utilizing both AND and OR codes to refine the search parameters. The data collection applying PICOS (Populations, Interventions, Comparisons, Outcomes, Study Design) as a full inclusion criteria framework to refine literature selection. Results: A total of 10 selected articles were eligible based on the criterias. Most reviewed articles show the beneficial effects of yoga as a complementary therapy for SUD. Yoga had positive effects to decrease several physical and psychological issues, also reduce addictive behaviors. Yoga is low cost and low risk treatment, both culturally acceptable and accessible treatment. Overall, yoga recommended as complemenntary therapy in drug rehabilitation. Conclusion: This study contributes to understanding the effects of yoga on substance use disorder. Yoga has positive effects on physiological, psychological, and behavioral domain. This review provides insight into promote yoga as complementary for comprehensive drug rehabilitation. A future meta-analysis can yield a quantitative assessment of yoga's efficacy as a therapeutic intervention.